Lipid dependence of connexin-32 gap junction channel conformations - Lavriha, Pia; Fluri, Carina; Hernández González, Jorge Enrique [UNESP]; Korkhov, Volodymyr M. (Springer Nature, 2025)
Connexin-32 (Cx32) gap junction channels (GJCs) mediate intercellular coupling in various tissues, including myelinating Schwann cells. Mutations in Cx32, such as W3S, are associated with X-linked Charcot-Marie-Tooth (CMT1X) disease. Lipids regulate Cx32 GJC permeation, although the regulatory mechanism is unclear. Here, we determine the cryo-EM structures of Cx32 GJCs reconstituted in nanodiscs, revealing that phospholipids block the Cx32 GJC pore by binding to the site formed by N-terminal gating helices. The phospholipid-bound state is contingent on the presence of a sterol molecule in a hydrophobic pocket formed by the N-terminus: the N-terminal helix of Cx32 fails to sustain a phospholipid binding site in the absence of cholesterol hemisuccinate. The CMT1X-linked W3S mutant which has an impaired sterol binding site adopts a conformation of the N-terminus incompatible with phospholipid binding. Our results indicate that different lipid species control connexin channel gating directly by influencing the conformation of the N-terminal gating helix.